2006
DOI: 10.5694/j.1326-5377.2006.tb00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Interface between residential aged care facilities and a teaching hospital emergency department in Western Australia

Abstract: Objective: To estimate the appropriateness of emergency department (ED) presentations by people aged ≥ 65 years living in residential care facilities. Design, setting and participants: Retrospective cohort study of older residents of residential care facilities who presented to the ED of the Royal Perth Hospital, Western Australia, between January and June 2002. Data were reviewed by an expert clinical panel. Main outcome measures: Appropriateness of ED presentation, presenting complaint, involvement of a gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
116
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(127 citation statements)
references
References 16 publications
8
116
1
2
Order By: Relevance
“…Twenty-nine articles met the inclusion criteria [3,4,8-10,15,18-41]. Two articles reporting on the same study were considered as one source [21,38].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-nine articles met the inclusion criteria [3,4,8-10,15,18-41]. Two articles reporting on the same study were considered as one source [21,38].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported low proportions of inappropriate admissions. For example, Bermejo et al [35] and Finn et al [3] reported on 1.6% and 13.1% of inappropriate emergency department visits, respectively; Becker et al [33] reported on 18% of preventable hospitalisation. Other studies documented high proportions of inappropriate admissions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, more recent studies from Canada and Australia determined that 85% of nursing home transfers were appropriate 74 75. Nevertheless, the Australian study identified evidence of primary care doctor involvement in only 25% of referrals, and a lack of clinical support for nursing home staff in general.…”
Section: Findings and Discussionmentioning
confidence: 97%
“…Despite this, approximately 60% of ED presentations lead to hospital admission [25, 26]. In an attempt to keep frail older persons at their place of residence during an acute illness, several MOC have been designed and tested.…”
Section: Introductionmentioning
confidence: 99%